Determination of free fatty acids in biological samples: Different ways to preparing samples - N. S. Morozova; V. A. Akmurzina; A. V. Matveev; A. Yu. Milentyev; D. I. Prokhorov; A. O. Ruzhitsky; G. M. Sorokoumova; A. A. Selishcheva; V. I. Shvets (Тонкие химические технологии, 2012)
Approaches to sample preparation for estimation of free fatty acids composition by gas chromatography are presented. These fatty acids are included in the total lipid extract of human plasma.